Cupcake Diaries : Katie Sprinkles & Surprises - Coco Simon (India Simon Spotlight, 2013)
When Katie$1 (Bs mom says it$1 (Bs time for Katie to meet her new boyfriend, Katie is excited and nervous. She thinks she$1 (Bs prepared, but she$1 (Bs shocked instead. Her mom$1 (Bs boyfriend is Jeff Green$1 (Bas in Mr. Green, a math teacher in her grade! Katie tries to act as normal as possible, but when mean girl Olivia finds out, she tells everyone that Katie is getting special treatment because her mom is dating a teacher. How can Katie stop Olivia and deal with all the new events in her life? It$1 (Bs the Cupcake Club to the rescue, as Katie$1 (Bs friends come to her defense, including an unexpected ally.s
Keywords: Realistic Fiction -- Realistic Fiction